Application of PDCA cycle in continuous quality improvement of nursing inventory records in the operating room (PDCA循环法在手术室护理清点记录单持续质量改进中的应用) - YIN Bei (尹蓓); WANG Yaling (王雅玲); QIU Murong (邱慕蓉) (中西医结合护理)
Objective To evaluate the application effect of PDCA cycle in continuous quality improvement of nursing inventory records in the operating room. Methods The PDCA nursing quality control team composed of five nursing staffs was established, and group members analyzed potential problems and countermeasures in writing of nursing inventory records. Conventional document writing quality control was adopted for 3000 copies of nursing inventory records from March 2022 to May 2022 (control group) , and the PDCA cycle management was used for 3000 copies from July 2022 to September 2022 (observation group). The defect rate of nursing inventory records was analyzed and compared between two groups. Results The qualified rate of nursing inventory records was 99. 27%(2978/3000)in the observation group, which was higher than 97. 53%(2924/3000)in the control group, with a significant difference(P＜0. 05). Conclusion Application of PDCA cycle in document writing may help nurses effectively analyze and improve the detailed and important problems in clinical practice, and form a relatively complete document quality control supervision system by establishing a quality improvement team, formulating measures, and supervising with other members of the department. Quality control by using PDCA cycle is effective to improve the qualified rate of nursing inventory records in the operating room, safeguard the legitimate rights and interests of both medical staffs and patients, and promote the continuous improvement of medical care quality. (目的 探讨运用PDCA循环提高手术室护理清点记录单合格率的效果。方法 由手术室5名护理人员组成PDCA护理文件质控小组, 分析手术室护理文件书写质量问题并提出改进措施。选取2022年3月—5月实施常规质量控制的3000份手术室护理清点记录单为对照组, 2022年7月—9月实施基于PDCA循环管理质量控制的3000份手术室护理清点记录单为观察组。分析两组书写缺陷发生情况, 对比手术室护理清点记录单书写规范率。结果 实施PDCA循环法实施后, 手术室护理清点记录单书写规范率为99. 27%(2978/3000), 高于实施前的97. 53%(2924/3000), 差异有统计学意义(P＜0. 05)。结论 文件书写质量控制中运用PDCA循环法, 对工作中细节且重要的问题进行分析、改进, 通过成立质量改进小组、制定措施, 与科室其他成员共同监管, 能够形成一个较为完善的文件质控监管体系, 从而提高手术室护理清点记录单合格率, 维护医患双方和合法权益, 促进医疗护理质量的持续改进。)